A Case Report on A Rare Variant of a Common Anomaly – Covered Bladder Exstrophy - Ravi, Saranya; Prabhakar, Thangavel; Agrawal, Vikesh; Tiwari, Abhishek; Sisodiya, Rajpal; Acharya, Himanshu (Iranian Journal of Pediatric Surgery, 2025)
Abstract Background: Variants of bladder anomalies are rare and often associated with other abnormalities of the genitourinary system. Covered bladder exstrophy, a rare variant within the exstrophy-epispadias complex, is one such example. Case Presentation: We report a case of a 2-year-old female presenting with covered exstrophy of the bladder. The patient exhibited intermittent swelling over the anterior abdominal wall since birth, which increased in size during urination. Examination revealed a midline abdominal wall defect covered by skin in the hypogastric region. Diagnostic imaging, including a micturating cystourethrogram and ultrasound, confirmed the presence of an anterior abdominal wall defect with diastasis of the pyramidalis muscle and a focal bladder mucosal defect with intact detrusor muscle continuity. Intervention: Surgical exploration revealed a smooth, globular structure with thinned walls and a vascular appearance herniating through the defect, confirmed to be the urinary bladder. Primary repair was performed, augmented with an onlay mesh hernioplasty using a polypropylene mesh. Outcome: The intraoperative period was uneventful, and the patient was alert and active postoperatively. Follow-up showed no complications, and the patient exhibited normal urinary function. Conclusion: This case highlights the importance of early diagnosis and surgical intervention in managing covered bladder exstrophy. The successful repair of the defect and the favorable postoperative outcome underscore the efficacy of the surgical approach used.